2007
DOI: 10.3354/meps341293
|View full text |Cite
|
Sign up to set email alerts
|

Top-down control of phytoplankton by oysters in Chesapeake Bay, USA: Comment on Pomeroy et al. (2006)

Abstract: Pomeroy et al. (2006) proposed that temporal and spatial mismatches between eastern oyster filtration and phytoplankton abundance will preclude restored stocks of eastern oysters from reducing the severity of hypoxia in the deep channel of central Chesapeake Bay. We refute this contention by presenting arguments, data, and model results, overlooked by these authors. Our analysis indicates that oyster populations living on extensive reefs along the flanks of the mainstem Bay could substantially reduce summer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…On the other hand, marine suspension-feeding benthic bivalves can effectively control phytoplankton growth, especially in shallow coastal systems (e.g., Prins et al, 1998;Dame and Olenin, 2005), leading to the suggestion that mussels, oysters and other reefforming benthic bivalves could potentially regulate phytoplankton sufficiently to reduce hypoxia in eutrophic coastal systems (e.g., Officer et al, 1982;Newell and Ott, 1999). A requirement for this to be effective is that benthic grazers must have access to upper mixed layer water where they can graze rapidly growing cells and retain organic matter in the shallow aerobic waters (e.g., Pomeroy et al, 2006;Newell et al, 2007). Although field-scale documentation of benthic grazing impacts mitigating coastal hypoxia is limited, several modeling studies have demonstrated potential effectiveness (e.g., Cerco and Noel, 2007;Banas et al, 2007).…”
Section: Internal Ecological Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, marine suspension-feeding benthic bivalves can effectively control phytoplankton growth, especially in shallow coastal systems (e.g., Prins et al, 1998;Dame and Olenin, 2005), leading to the suggestion that mussels, oysters and other reefforming benthic bivalves could potentially regulate phytoplankton sufficiently to reduce hypoxia in eutrophic coastal systems (e.g., Officer et al, 1982;Newell and Ott, 1999). A requirement for this to be effective is that benthic grazers must have access to upper mixed layer water where they can graze rapidly growing cells and retain organic matter in the shallow aerobic waters (e.g., Pomeroy et al, 2006;Newell et al, 2007). Although field-scale documentation of benthic grazing impacts mitigating coastal hypoxia is limited, several modeling studies have demonstrated potential effectiveness (e.g., Cerco and Noel, 2007;Banas et al, 2007).…”
Section: Internal Ecological Processesmentioning
confidence: 99%
“…The rapid increase in surface water temperatures (∼0.7 • C) that occurred over two decades around 1985 (Kaushal et al, in press) would be sufficient to reduce O 2 saturation level by ∼0.20 mg l −1 and possibly increase respiration by ∼5-10% (Sampou and Kemp, 1994). The relative abundance and filtering capacity of the eastern oyster (Crassostera virginica) in Chesapeake Bay have declined by almost 100-fold over the past 150 years due to over-fishing and two disease outbreaks (Newell, 1988;Newell and Ott, 1999;Newell et al, 2007). The drought-induced final decline in oyster harvest during the 10-15 yr around 1985 was ∼10% of this overall drop between 1900 and the present (Fig.…”
Section: Chesapeake Baymentioning
confidence: 99%
“…Therefore, restoration of oyster reefs has received increasing attention and investment from coastal municipalities. However, the wisdom of pursuing restoration is controversial [11][12][13][14][15][16]. Part of this disagreement may stem from differences in how the goals of each restoration project are defined, the complexity of ecosystem services rendered by oysterreefs, and whether benefits from all of these services are includedin the assessment of restorationsuccess [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…
debated [11,12,14,15], but less research has been devoted to the effect of oyster reefs on the surrounding sediment. Reefs act to attenuate wave energy, possibly facilitating deposition of fine sediment [8]; this process may work in concert with oyster filtration to increase light penetration that may then shift ecosystems towards more benthic primary producers [6].
…”
mentioning
confidence: 99%
“…This argument has been criticized as inaccurate, emphasizing the need for nutrient removal (Boesch et al 2001). While it would seem obvious that both influences contribute to degraded estuarine waters, disagreement on the main influence still leads to situations like the pro and con discussions on restoration of conditions in the Chesapeake Bay by top-down control, i.e., enhancement of higher trophic level consumers (Newell et al 2007), as opposed to bottom-up nutrient controls (Pomeroy et al 2007). These different characterizations of the problem can lead to quite different remedial action.…”
mentioning
confidence: 99%